Elected legislatures in sub-saharan Africa: Attitudes of citizens from 18 countries towards legislatures, with a particular focus on Mozambique, its assembly and parliamentarians - Azevedo, Elisabete (Department of Political Studies, 2014)
Elected multi-party assemblies have existed in Africa on average for no more than two decades. Consolidating democracy and improving the lives of ordinary citizens demands guardian parliaments. Parliaments are comprised predominantly of politicians and, interconnected with citizens and executives, are perceived as core institutions of representative democracies. This dissertation seeks to contribute to a better understanding of African multiparty parliaments and their role in consolidating democracy. The study seeks to comprehend the links between citizens and their elected parliaments in 18 African countries, in the process attempting to predict the prospects of these new democracies. It also focuses on the Assembly of Mozambique to attempt an understanding of the evolution, capacity and functioning of an emerging parliament. The study investigates the perceptions of Mozambican civil leaders toward their parliament, and it looks at the perceptions of Mozambican parliamentarians concerning their roles and their relations with the electorate, and concerning the Assembly’s capacity and powers. This is critical to understanding how democracy has been and will be exercised, since parliamentarians are at the forefront of the process. Each parliament has distinctive characteristics. However, there are common features based on their age and origin. The development of the Mozambican Assembly since the monoparty regime illustrates the challenges and achievements that African parliaments have undergone in the transition to democracy. The findings reveal that African citizens distinguish between presidents and parliaments, which is important given the legacy in Africa of strong executives led by dominant presidents. They also reveal that citizens value the gains made by the multiparty regimes and that parliaments as lawmakers are preferred to presidents. In most countries surveyed, citizens, on average, gave positive evaluations of their parliaments, especially concerning their trustworthiness. Political characteristics outweigh socio-economic status in influencing how citizens perceived parliaments. Party allegiance and perception of electoral fairness are the factors that most influenced how citizens perceived their parliaments. Interviews with Mozambican MPs revealed their frustration over the influence of the Assembly over the national budget. In the MPs’ opinions, direct foreign aid to the budget reduced parliament’s role to that of a rubber stamp, weakening the role of MPs. Mozambican civic leaders saw parliament as an indispensable and critical institution, and they expressed frustration with the extreme party-centricity of MPs, which is perceived as normal by MPs. Distrust between these groups reinforces the sentiment among ruling party members that the party deserves protection. In democracies, MPs from different parties are political opponents and not enemies. In Mozambique, the transition from enemy to adversary is not yet complete. While fragile, parliament has been the only space in Mozambican society where political parties can interact.